(3fUGH GdJYRjRs - (3fUQ Hf YHO GdQMje Hf YHO GdQMefs
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj TQY GdMOhO RGLQI ddCfGe CeG HYO abO bGd GdYHO GdVYja deG QCjJ GdfGS jQJcHhf GdeYGUj hGdefcQGJ aLeYJ eNJUQ GdeSGFd djchf CQab hCSgd Ydi WGdHg hSejJg HfUGH GdJYRjR GdeOeI hajg (B( (3cPG (B) (3aUhd aUd aj eG gjiI GdJYRjR hGdTQYjI hHjGf GdaQb Hjfg hHjf GdMOs
(3BNQgG (B:s
(3aj GdSQGLjI EPG PcQ aj GdSLd Cf GdTghO TgOhG Ydi ehGabI GdOYhi hde jZjQ GdTgGOI dG jUM EdG EPG cGf GdbGVj YGdeG cGedG MejOj (B( (3cPG (B)s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3Gdabg GdMfHdjs